Ex vivo Expanded Regulatory B Cells Promote Allograft Survival through IL-10-dependent Pathway. (July 2018) - Lee, Kang Mi; Deng, Kevin; Kojima, Lisa; Dai, Chen; Rickert, Charles; Yeh, Heidi; Markmann, James
Abstract : Introduction: Immunomodulatory capacity of B cells make them a promising therapeutic tool for autoimmune and alloimmune response in patients. We found that transplant tolerance induced by a short course of anti-CD45RB was B cell-dependent. Subsequently, adoptive transfer of regulatory B cells from tolerant to naïve hosts transferred tolerance. Recently we have expanded naive B cells in an ex vivo culture system. In this study, we evaluated the efficacy of their phenotype, function, and mechanism to promote allograft survival. Methods: To generate ex vivo expanded regulatory B cells, splenic B cells were isolated from normal B6 mice and cultured on monolayers of irradiated NIH-3T3 cells expressing the CD40 T cell ligand with supplements of anti-TIM-1, IL-4, IL-21, and BAFF for 8 days. For adoptive transfer experiments, theses cultured B cells were purified by cell sorting to avoid 3T3 cell contamination. The sorted B cells were then IV injected into diabetic B cell-deficient μMT mice that received simultaneous Balb/c islet transplant. Allograft survival was measured by blood glucose level. To identify key mechanisms of ex vivo expanded regulatory B cells in vivo, we also expanded B cells isolated from IL-10-/-, TGFβ-/-, IL-4-/-, and OB1 mice in addition to wild type B6 mice. B cell surface phenotypes and intracellular cytokine expression were detected by immunofluorescence staining and analyzed by flow cytometry. Results: Ex vivo expanded B cells showed a high-level expression of TIM-1, CD9, and CD25, which are associated with regulatory B cell markers, and increased expression of CD80/CD86 activation markers. We observed that adoptive transfer of ex vivo expanded B cells promoted graft survival comparing to naïve B cells (p value=0.0155*) and half of the recipients showed indefinite graft survival. TIM1+ B cells were sorted among the expanded B cells and then transferred to diabetic μMT mice. These mice also accepted allo-islet grafts well (P value=0.036*). Regulatory B cells have been demonstrated to be IL-10-dependent in other models, thus we tested if ex vivo expanded regulatory B cells are also IL-10-dependent. Transfer of ex vivo expanded IL-10 deficient B cells resulted in rapid rejection of all allograft without prolongation compared to wild-type B cells (P value=0.040*). In addition, B cells from TGFβ-/-, IL-4-/-, and OB1 (BCR transgenic mice) were unable to significantly prolong graft survival. Conclusion: The ex vivo culture system quantitively expands B cells and qualitatively develops B cells into regulatory B cells. These regulatory B cells prolong allografts via an IL-10, TGFβ, IL-4-dependent pathway and a diverse B cell repertoire is also required. These findings may provide a novel and effective in vivo treatment for transplantation settings.